SEM ANALYSIS OF ADDITIVELY MANUFACTURED STAINLESS STEEL 316L AND CONVENTIONAL SAMPLES - Constantin Alex Sumanariu; Catalin Gheorghe Amza; Cristian Giolu; Silviu Stanciu; Madalin Savu (Nonconventional Technologies Review)
This research paper presents for discussion a comparative investigation of Stainless Steel 316L samples fabricated by additive manufacturing (AM) and conventional production techniques, utilising Scanning Electron Microscopy (SEM). Within the study the microstructural distinctions between the two methods is examined with emphasising on grain shape and void distribution. SEM imaging is used to identify the influence of additive manufacturing on material characteristics, including the development of finer microstructures and increased residual porosity relative to traditionally produced SS316L. The findings have considerable significance for the use of SS316L in sectors necessitating exact mechanical qualities and thermal resistance.